The safety and effectiveness of sintilimab versus camrelizumab, both plus targeted drugs, in advanced hepatocellular carcinoma - Zhao, Chenglong; Zhu, Qiongni; Qian, Xiaoyan; Fu, Zhonghua; Zhang, Wei; Wang, Yaqin (Frontiers in Immunology, 2025)
ObjectivesWe aimed to evaluate the effectiveness and safety of sintilimab versus camrelizumab, both plus targeted drugs, for advanced hepatocellular carcinoma (HCC) in the real world. Then the effectiveness was compared between sintilimab-lenvatinib and camrelizumab-apatinib.MethodsPatients diagnosed as advanced HCC were included from January 2017 to December 2023. They were concurrently treated with targeted drugs and sintilimab or camrelizumab. Progression-free survival (PFS), overall survival (OS), and adverse events (AEs) were assessed. The subgroups analysis of PFS and OS based on baseline characteristics and univariate and multivariate COX analysis were done to test for heterogeneity of data and correct for confounding factors. Then subgroup analysis of sintilimab-lenvatinib versus camrelizumab-apatinib was conducted.ResultsA total of 300 eligible HCC patients (199 in sintilimab group and 101 in camrelizumab group) were included in our study. No significant difference in PFS (p=0.47) and OS (p=0.51) was observed between sintilimab and camrelizumab groups. The median PFS (mPFS) was 262 days in sintilimab group, and 220 days in camrelizumab group, and neither group has reached the median OS. There was no difference in AEs between two groups also. The effect of sintilimab and camrelizumab on PFS and OS based on baseline characteristics was consistent with primary outcomes, except for other metastatic sites and lenvatinib in terms of OS. Multivariable Cox analysis identified the number of metastatic sites ≥2 and AFP level ≥400ng/mL as independent predictors of shorter PFS and OS, but they had no effect on the primary outcomes. In subgroup analysis, the PFS and OS of sintilimab -lenvatinib and camrelizumab-apatinib in first-line treatment of advanced HCC were not clinically different, although sintilimab-lenvatinib had a longer mPFS (301 days in sintilimab-lenvatinib group vs. 194 days in camrelizumab-apatinib group).ConclusionsSintilimab and camrelizumab, both plus targeted agents, have equal clinical effectiveness and incidences of AEs. The effectiveness of sintilimab-lenvatinib and camrelizumab-apatinib are similar in first-line treatment of advanced HCC, despite a slight superiority in sintilimab-lenvatinib is observed.